2019
DOI: 10.1007/s10803-019-04004-1
|View full text |Cite
|
Sign up to set email alerts
|

Do Student Characteristics Affect Teachers’ Decisions to Use 1:1 Instruction?

Abstract: One-to-one instruction is a critical component of evidence-based instruction for students with autism spectrum disorder, but is not used as often as recommended. Student characteristics may affect teachers' decisions to select a treatment and/or implement it. This study examined the associations between students' clinical and demographic characteristics and teachers' reported use of discrete trial training (DTT) and pivotal response training (PRT). Children's higher sensory symptoms, lower social approach, low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…In Nuske et al (2019), age was not associated with implementation of 1:1 instruction. These findings suggest that teachers are not considering students' age when implementing either PRT or DTT.…”
Section: Current Knowledgementioning
confidence: 78%
See 4 more Smart Citations
“…In Nuske et al (2019), age was not associated with implementation of 1:1 instruction. These findings suggest that teachers are not considering students' age when implementing either PRT or DTT.…”
Section: Current Knowledgementioning
confidence: 78%
“…Findings from Nuske et al (2019) also suggested that teachers did not differentially use DTT or PRT based on child characteristics, despite the theoretical notion that different profiles of children may be better suited to one over the other (Vivanti 2017). Evidence suggests that matching children with ASD to certain treatment styles based on their pretreatment behavioral profile may support positive outcomes (Schreibman et al 2009;Sherer and Schreibman 2005).…”
Section: Current Knowledgementioning
confidence: 99%
See 3 more Smart Citations